Exploring Risk Management Issues in the Technological Sector: The Effect of the Use of Derivatives Hedging on Technology Firms’ Value - Ferri, Salvatore; Tron, Alberto; Colantoni, Federico; Savio, Riccardo (Senate Hall, 2022)
Entrepreneurship is synonymous with “bearing risk”. In a technological context, the risks are much higher. The implementation of risk management instruments is therefore essential for entrepreneurs in the technological industry. However, how the use of derivatives hedging impacts the market value of technology firms remains unaddressed. To expand upon entrepreneurship literature in terms of risk management, we develop a new multidisciplinary theory that integrates risk management theories with entrepreneurship. By applying various methodologies (fixed-effect, pooled OLS, and system GMM) to our sample of 81 firms —listed between 2007-2020 in the Stoxx Europe 600 and operating in the Telecommunication and Information Technology industries— we reveal that the use of this risk management instrument does not impact upon technology firm value, measured as Tobin’s Q. These results offer entrepreneurs a better understanding of the uselessness of using derivatives hedging to increase technology firm value in the technological industry.
Keywords: Derivatives|Hedging|Risk management|Corporate decisions|Entrepreneurship